Targeting prion-like protein doppel selectively suppresses tumor angiogenesis - Al-Hilal, Taslim A.; Chung, Seung Woo; Choi, Jeong Uk; Alam, Farzana; Park, Jooho; Kim, Seong Who; Kim, Sang Yoon; Ahsan, Falchrul; Kim, In-San; Byun, Youngro (AMER SOC CLINICAL INVESTIGATION INC, 2016)
Controlled and site-specific regulation of growth factor signaling remains a major challenge for current antiangiogenic therapies, as these antiangiogenic agents target normal vasculature as well tumor vasculature. In this article, we identified the prion-like protein doppel as a potential therapeutic target for tumor angiogenesis. We investigated the interactions between doppel and VEGFR2 and evaluated whether blocking the doppel/VEGFR2 axis suppresses the process of angiogenesis. We discovered that tumor endothelial cells (TECs), but not normal ECs, express doppel; tumors from patients and mouse xenografts expressed doppel in their vasculatures. Induced doppel overexpression in ECs enhanced vascularization, whereas doppel constitutively colocalized and complexed with VEGFR2 in TECs. Doppel inhibition depleted VEGFR2 from the cell membrane, subsequently inducing the internalization and degradation of VEGFR2 and thereby attenuating VEGFR2 signaling. We also synthesized an orally active glycosaminoglycan (LHbisD4) that specifically binds with doppel. We determined that LHbisD4 concentrates over the tumor site and that genetic loss of doppel in TECs decreases LHbisD4 binding and targeting both in vitro and in vivo. Moreover, LHbisD4 eliminated VEGFR2 from the cell membrane, prevented VEGF binding in TECs, and suppressed tumor growth. Together, our results demonstrate that blocking doppel can control VEGF signaling in TECs and selectively inhibit tumor angiogenesis.
Keywords: MOLECULAR-WEIGHT HEPARIN; BRAIN ENDOTHELIAL-CELLS; PRP-LIKE PROTEIN; IN-VIVO; BLOOD-VESSELS; ORAL DELIVERY; VEGF; MICE; METASTASIS; GROWTH